PEMBUATAN DAN KARAKTERISASI ADSORBEN KITOSAN–SILIKA DAN PENGAPLIKASIAN TERHADAP ADSORPSI ION Cd2+ - Nisa, Muflihatu Khoiratun; Lianasari, Ika Yekti; Koesnarpadi, Soerja (JURNAL ATOMIK, 2022)
The Research has been conducted on the synthesis of chitosan-silica adsorbents from chitosan and silica derived from TEOS (Tetraethyl Orthosylicate). The chitosan-silica was made by mixing chitosan solution and silica soles that were previously chitosan we were added with acetic acid and silica solution we were added with aqueous solution, ethanol and HCl(p). The result from characterization of FT-IR chitosan-silica adsorbents indicates the presence of OH, NH2, Si-O, Si-O-Si, chitosan adsorbents that only have OH and NH2 groups and silica adsorbents that only have OH, Si-O and Si-O-Si groups. Application of chitosan, silica and chitosan-silica adsorbents to adsorp Cd2+ ion. Cd2+ ion concentration after adsorption was determined by atomic absorption spectrophotometer (AAS). Adsorption Cd2+ ion in chitosan-silica successfully indexed Cd2+ by 98.67% while for chitosan adsorbents by 97.87% and while silica adsorbents by 79.45%. The Sem results showed that when adsorbents before soaking with Cd2+ it was seen that the morphology of the surface of the pores adsorbent there is still a cavity then when after soaking with Cd2+ pores filled by ions Cd2+.